Making the New Indonesia Work for the Poor - World Bank (Washington, DC, 2012)
Indonesia stands at the threshold of a new era and at an important juncture of its history. After the historic economic, political and social upheavals at the end of the 1990s, Indonesia has started to regain its footing. The country has largely recovered from the economic and financial crisis that threw millions of its citizens back into poverty in 1998 and saw it regress to a low-income status. Recently, it has once again crossed the threshold, making it one of the world's emergent middle-income countries. Likewise, poverty rates that increased by over one-third during the crisis fell back to pre-crisis levels in 2005, despite rising somewhat in 2006 largely driven by hefty rice price increases in late 2005 and early 2006. Meanwhile, politically and socially Indonesia has seen some major transformations: it is now a country with a vibrant emergent democracy, a newly decentralized government, and far greater social openness and public debate. The purpose of this report is to identify the nature and key constraints to poverty reduction in today's Indonesia and to provide concrete recommendations on how Indonesia can move forward to achieve its poverty reduction objectives. It aims to contribute to the policy debate and decision-making process in Indonesia by putting forth: (i) new and more comprehensive analysis of empirical poverty diagnostics; and (ii) suggestions on concrete policies and programs for a strategic action-plan to achieve Indonesia's stated poverty-reduction objectives. This report lays out how Indonesia can better align policies and programs to achieve the key poverty indicators in which Indonesia is lagging and that are identified by planning documents such as the National Strategy for Poverty Reduction (SNPK) and Medium-Term Development Plan (RPJM).